Answer:
x= 2.468374946 or x= -0.135041612
Step-by-step explanation:
Give each number a term
[tex] {3x}^{2} - 7x - 1 = 0 \\ {ax}^{2} + bx + c = 0[/tex]
Write out this formula and substitute
[tex]x = \frac{ - b \binom{ + }{ - } \sqrt{ {b}^{2} - 4ac } }{2a} \\ x = \frac{ - ( - 7) \binom{ + }{ - } \sqrt{ {( - 7)}^{2} - 4(3)( - 1)} }{2(3)} [/tex]
Expand the brackets
[tex]x = \frac{7 \binom{ + }{ - } \sqrt{41 + 12} }{6} \\ x = \frac{7 \binom{ + }{ - } \sqrt{61} }{6} [/tex]
Solve for each
[tex]x = \frac{7 + \sqrt{61} }{6} \\ x = 2.468374946[/tex]
[tex]x = \frac{7 - \sqrt{61} }{6} \\ x = - 0.135041612[/tex]